The Influence Between Gender on Tax Compliance with Love of Money as a Moderation Variable - Yastika Rosaria Abung; Theresia Woro Damayanti (International Journal Labs, 2023)
Indonesia has experienced a very rapid decline in the tax ratio due to economic pressures arising from the Covid-19 pandemic. With the achievement of a gross domestic product (GDP) of IDR 15,434.2 trillion in 2020, the tax ratio in a broad sense in 2020 was only 8.94% from the previous year of 10.74%. This study aims to find out whether gender has an effect on tax compliance, and whether the love of money can moderate the influence of gender on tax compliance. This study used primary data taken by distributing questionnaires to taxpayers, especially to MSME owners in Salatiga with a sample of 96 respondents. This research is descriptive and quantitative and uses a simple linear regression analysis method and also uses Moderated Regression Analysis (MRA). The results of this study prove that the influence between gender and tax compliance, as well as the love of money, can weaken the relationship between gender and tax compliance.